Augmented reality based map navigation (AR-BAMAN) - Ling, Kah Wei (Universiti Malaysia Sarawak, (UNIMAS), 2005)
In this era of information technology, computer science is becoming more and more important. Augmented Reality (AR), which is part of the computer science field, is becoming more popular. AR is a combination of real world object together with computer-generated objects. AR has been successfully implemented in historical sites, magic books, military equipment and other fields. Augmented Reality Based Map Navigation AR-BAMAN is a research and application on AR field. This system is to enhance current UNIMAS map. With AR-BAMAN, user will be able to navigate their way around UNIMAS easier. This is because AR-BAMAN is able to display the 3D objects (buildings) to ‘emerge’ on the UNIMAS map in the computer when the map is put under the web camera. The 3D objects are build using Virtual Reality Mark Up Language (VRML). The map of UNIMAS is designed using markers. ARToolkit is used to recognize the marker and display the VRML objects on top of it. The main feature of this system is that it recognized the markers (real object), combine with computer generated objects and display it on the monitor. This report discussed the introduction of AR-BAMAN, background review, requirements and analysis, system design, system implementation, testing, and future works.